Analisis Kewajiban Belajar Mengajar Di Tinjau Dari Sudut Pandang Hadits - Atik Devi Kusuma; Merli Anggelia; Royhana Safitri; Zaky Raihan Febrianto; Wismanto Wismanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Learning to teach is everyone's obligation, as taught by the Prophet Muhammad, to his people to continue learning throughout life. And also in the Qur'an it is explained in surah Al-Mujadilah verse 11 that Allah raises the status of believers and people of knowledge. The aim of this research is to reveal the arguments from the hadith which explain the obligation to learn and teach as well as the obligation to seek knowledge in Islam. The method used in this research is a qualitative method with a library approach, the main data sources are reading materials from books, magazines, journal articles and hadith books. The results of this research show that there are many hadith propositions that explain the obligation to learn to teach for every Muslim, starting from learning to teach from birth to the grave. Up to the priority of those who learn and those who teach.